If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -1x = 3x + 17 Reorder the terms: -7 + -1x = 17 + 3x Solving -7 + -1x = 17 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -7 + -1x + -3x = 17 + 3x + -3x Combine like terms: -1x + -3x = -4x -7 + -4x = 17 + 3x + -3x Combine like terms: 3x + -3x = 0 -7 + -4x = 17 + 0 -7 + -4x = 17 Add '7' to each side of the equation. -7 + 7 + -4x = 17 + 7 Combine like terms: -7 + 7 = 0 0 + -4x = 17 + 7 -4x = 17 + 7 Combine like terms: 17 + 7 = 24 -4x = 24 Divide each side by '-4'. x = -6 Simplifying x = -6
| 2x^2-50=24 | | 1x-4+1x=5(9-4x) | | 2-8x+1(x-4)=2(x-7) | | 6x+3=2x+31 | | m-14.6=9.74 | | 4+2x=5x-2 | | w-8=32 | | 4y-8=5y-1 | | 17dl=l | | 3x+4=-36-5x | | x=2*8+77 | | 16+5x= | | 3x+4=-35-5x | | (2x+5)x(7x-2)=(4x+3)x(5x-1)+82 | | 4(d-7)=524 | | X-4X+3Y+9Y-12=0 | | 5x+3x+120=360 | | 6*x*y-12=0 | | x+3x-4= | | f(x)=2x^4-3x | | y-1=-6/7(14) | | 3(2x+3)=45 | | (2x+5)=27 | | (x-5)10+(1-2x)15=(3-x)14 | | x-12y=-36 | | 80-6x=7x+16 | | 7(9)+9y=63 | | 3y-5x=0 | | 3y+2(-3)=-6 | | (8x-8)/7-4(x+4)/7+7=8 | | x^2-24x-51=0 | | x^3-24x^2-51x=0 |